IN VITRO ANTIOXIDANT AND CYTOTOXIC ACTIVITY OF RUTIN AND PIPERINE AND THEIR SYNERGISTIC EFFECT - Yadala, Prapurnachandra; Viswanathswamy, A. H. M. (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The objective of the present study was to evaluate the antioxidant and cytotoxic activities of Rutin and Piperine and their synergistic effect. Methods: The Oxidative activity of Rutin, Piperine, and combination of both was confirmed by the level of Superoxide radical (SOD), Nitric oxide (NO), and Reducing power method (RO), Cytotoxic activity was also measured by using brine shrimp lethality bioassay. Results: The present study showed that combination of Rutin and Piperine showed enhanced antioxidant activity in SOD and NO compared to individuals with IC50 values 27.18Â±0.59 Âµg/ml and 22.00Â±0.15 Âµg/ml respectively and also produced good reducing power activity. All samples showed a potent cytotoxic effect, combinational sample showed a more potent effect than the standard potassium dichromate with LC50 3.96 Âµg/ml. Conclusion: Therefore, the present study demonstrated that the combination of Rutin and Piperine exhibits synergistic antioxidant and cytotoxic effect and the study thus provide more insight into the mechanism of the hepato protective action of the combinational sample for the management of hepatotoxicity. Keywords: Rutin, Piperine, Antioxidant, Cytotoxic, SOD, NO, RO Â